Parenting Profiles in Arranging Child Discipline (Study in Junior High School 13 Padang) - Rezi Kumala Sari; Netrawati Netrawati (Jurnal Neo Konseling, 2019)
Based on the phenomenon that researchers can field when conducting interviews with some BK teachers and students found that there are students who play truant, arriving late was due to parents lacking in the formation of discipline so as to make children negligent in school. This study aims to: (1) describe how parental authoritarian parenting in shaping child discipline, (2) describe how parental democratic parenting in shaping child discipline, (3) describe how parental permissive parenting in shaping child discipline.This research is a quantitative descriptive type of research. The total population of 546 and a sample of 124 students were selected using the Simple Random Sampling technique. The data collection tool used was a questionnaire. Data were analyzed using statistical techniques, namely percentage formulations.The results revealed that (1) parental authoritarian parenting in shaping child discipline in SMP Negeri 13 Padang was in the very high category, (2) democratic parenting was in the high category, (3) permissive parenting was in the very high category. (4) based on the three types of parenting, the more dominant applied in shaping the discipline of children in SMP Negeri 13 Padang is permossive with a percentage of 73.21%. Based on the research findings, it is suggested to (1) parents are expected to be able to apply appropriate parenting in shaping the discipline of children, (2) furthermore BK teachers are expected to establish good communication with parents and work together in applying proper parenting to children.